Fenomena Penggunaan E-Commerce terhadap Perilaku Konsumsi Mahasiswa - Dwi Sartika; Mufidhatul Ulya; Fia Fauza Azzahra; Irnawati Irnawati; Fina Nur Hidayati; Didi Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The use of E-Commerce platforms has a significant impact on students' shopping patterns and consumption behavior. This article aims to analyze the factors that influence students in choosing to shop through E-Commerce and its impact on students' consumptive behavior from the perspective of consumption theory and modernization theory. The method used in this research is a qualitative approach, with sources collected through literature studies, data analysis, validity of analysis with data triangulation techniques. The results show that factors such as ease of use, price, product quality, availability of goods, emotional benefits, and tangible evidence influence students in choosing to shop through E-Commerce. The impact is a significant change in students' consumption patterns, which includes satisfaction with purchases, ease of product access, but also uncertainty about future needs and changes in shopping priorities. The implication is the importance of financial awareness and wise financial management skills for university students in dealing with the use of E-Commerce to minimize the negative impacts and maximize the benefits in improving their quality of life.